Liver Transplant for Nonhepatocellular Carcinoma Tumors: A Review of Expanding Indications in Nontraditional Transplant Oncology - Wehrle, Chase J.; Fares, Sami; Shanmugarajah, Kumaran; Wakam, Glenn; Calderon, Esteban; Kusakabe, Jiro; Satish, Sangeeta; Linganna, Maureen Whitsett; Khalil, Mazhar; Pita, Alejandro; Kim, Jae-Keun; Fujiki, Masato; Kwon, David C.H.; Schlegel, Andrea; Miller, Charles; Hashimoto, Koji; Aucejo, Federico (Digestive Disease Interventions, 2024)
Liver transplantation (LT) is a life-saving procedure most well-known in the curative treatment of cirrhosis or end-stage liver disease. The approach is also well established for hepatocellular carcinoma (HCC) within Milan or other similar criteria. However, LT is increasingly utilized as the treatment for other primary and secondary liver cancers, including cholangiocarcinoma, colorectal cancer liver metastasis, neuroendocrine tumor, and angiosarcoma. We aim to review indications for LT for non-HCC hepatic malignancies.
Keywords: liver transplantation; transplant oncology; selection criteria